Cardiac calcified amorphous tumor with sustained ventricular tachycardia. (May 2022) - Yamana, Fumio; Domae, Keitaro; Shirakawa, Yukitoshi; Takahashi, Toshiki; Hao, Hiroyuki
Cardiac calcified amorphous tumors are rare non-neoplastic intracavitary masses with unknown cause. A 60-year-old man presented with sustained ventricular tachycardia. Transthoracic echocardiography and contrast-enhanced angio-computed tomography demonstrated an expanding 73 × 40 mm sized calcified mass in the left ventricle. He underwent successful total removal of the mass and cryo-ablation at the normal myocardial border. Histopathological examination confirmed a diagnosis of cardiac calcified amorphous tumors. The postoperative course was uneventful, without ventricular tachycardia recurrence. To our knowledge, this is the first reported case of confirmed cardiac calcified amorphous tumors causing ventricular tachycardia and treated by surgical resection combined with cryo-ablation.